Resilience, mindfulness, and self-efficacy as predictors of foreign language anxiety among EFL learners - Saleh, Shoeb; Abdel-Al Ibrahim, Khaled Ahmed; Suleiman Alsadi, Mohammad Mahmoud; Elsayed Hassan, Eid Awad Abd; Abdullatif, Ali; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
Background: Foreign language anxiety remains one of the most persistent emotional barriers in English as a Foreign Language (EFL) learning. Although anxious learners may be motivated and hardworking, anxiety can narrow attention, reduce willingness to communicate, interrupt retrieval during performance, and make ordinary classroom tasks feel evaluative. At the same time, educational psychology has shown that learners are not passive recipients of stress. They enter the classroom with personal resources such as resilience, mindfulness, and self-efficacy, and these resources may change how anxiety is experienced, interpreted, and managed. Objective: This article develops a research-based model in which resilience, mindfulness, and English learning self-efficacy predict foreign language anxiety among EFL learners. The article is written as a full manuscript draft for adaptation into an empirical study. Because no dataset was provided, it does not report fabricated numerical findings; instead, it offers a theoretically grounded review, a transparent quantitative design, hypotheses, and an interpretation plan that can be implemented with real data. Methodology: The proposed study uses a cross-sectional quantitative design with EFL learners in secondary-school or university contexts. The recommended instruments include the Foreign Language Classroom Anxiety Scale, an academic or general resilience scale, a mindfulness awareness scale, and an English learning self-efficacy scale. Data analysis would involve reliability testing, descriptive statistics, Pearson correlations, multiple regression, and, where the sample is large enough, structural equation modelling. Expected contribution: The model expects resilience, mindfulness, and self-efficacy to be negatively associated with foreign language anxiety, with self-efficacy likely to function as the most direct classroom-linked predictor. Resilience is expected to support recovery from failure and persistence in difficult tasks, while mindfulness is expected to reduce rumination and help learners notice anxiety without becoming controlled by it. Conclusion: The article argues that anxiety reduction in EFL classrooms should not be limited to relaxation advice or test preparation. A more sustainable approach is to design classrooms that build confidence through mastery experiences, normalize setbacks, cultivate reflective awareness, and treat anxiety as a manageable part of learning rather than a sign of linguistic inadequacy.